Patterns of Compartment Involvement in End‐stage Knee Osteoarthritis in a Chinese Orthopedic Center: Implications for Implant Choice. Issue 3 (28th August 2018) - Wang, Wei‐jun; Sun, Ming‐hui; Palmer, Jonathan; Liu, Fei; Bottomley, Nicholas; Jackson, William; Qiu, Yong; Weng, Wen‐jie; Price, Andrew
Abstract : Objectives: Knee osteoarthritis (OA) is a prevalent disease in the elderly, causing pain and contributing to poor quality of life. Surgical intervention, such as knee arthroplasty, can be used in those with end‐stage knee OA. Total knee arthroplasty (TKA) is one of the most common surgical procedures for end‐stage knee OA, with promising clinical outcomes. However, a large proportion of patients with isolated compartment OA can be treated with unicompartmental knee arthroplasty (UKA) instead. UKA has shown better patient‐reported functional outcomes, and lower mortality and major complication rates than TKA. The percentage of UKA in knee arthroplasty varied in different orthopedic centers, and we believed that the requirement for UKA was underestimated in many centers. A retrospective study was carried out on our Chinese patient population presenting for knee arthroplasty; it aimed to identify the proportion of patients that might be suitable for UKA. Methods: A retrospective cross‐sectional study of 155 consecutive patients (168 knees) awaiting TKA for end‐stage primary OA was performed. The pattern and grade of OA was recorded from preoperative weight‐bearing anteroposterior and non‐weight‐bearing lateral radiographs. The medial, lateral, patellofemoral compartment was given an individual Kellgren–Lawrence grade on the radiographs, and those grade ≥3 were defined as end‐stage OA. The compartments involvement was established then. The integrity of the anterior cruciate ligament (ACL) was determined by the modified Keyes classification on lateral radiographs. The applicability for total or partial knee arthroplasty was determined according to the compartments involvement. Results: Medial compartment involvement was found in 154 (91.7%) knees, while the involvement of the lateral compartment and patellofemoral joint was found in 54 (32.1%) and 57 (33.9%) knees, respectively. Eighty‐one (48.2%) of the knees showed medial compartment OA with or without patellofemoral joint involvement, and modified Keyes classification grade 1, indicating an intact ACL, and, hence, potential suitability for medial UKA. Isolated lateral OA indicating possible suitability for lateral UKA was identified in 11 knees (6.5%). No patients showed isolated patellofemoral joint OA. The other 76 (45.2%) knees could be treated by TKA. Conclusions: The medial compartment was the most commonly affected in our Chinese patients indicated for knee arthroplasty. More than half of the patients in this group could be treated by either medial or lateral UKA.